Scientific Research on the Production of plant-based Meat Analogs using the Wet Extrusion Process - Antanas Sarkinas; Aelita Zabulione; Lina Traksele; Natalja Makstutiene; Alvija Salaseviciene (Chemical Engineering Transactions, 2023)
It is more and more necessary to select and provide model systems that fit to personalised nutrition, avoiding usage of main allergens. It can be achieved by combining raw materials of various origins, extracted using sustainable technologies, but at the same time maintaining the qualitative and quantitative characteristics of the product acceptable to specific user groups. Our research is distinguished by the processing of vegetable press-cakes and their combination with protein matrices, as well as the determination of the properties of these matrices. New methods of raw material processing can increase the bioavailability of essential nutrients in the raw material and in the matrix of final products and can promote positive changes in the microbiota. The consumption of fibrous materials is constantly growing, new sources of fibres are being sought, fibre-enriched food matrices are being developed, and consumer acceptability is being assessed. The aim of this study is to analyse the possibilities of applying innovative wet extrusion technology to produce raw meat analogs by composing products with optimal composition and sensory properties, testing a new, non-thermal high-pressure processing preservation method. When developing models for the processing of matrices of plant and animal raw materials using high-pressure technology, for varying parameters of pressure, time, packaging and duration, it was established that the high-pressure exposure model must be selected taking into account the composition and properties of the product, the purposeful application of other microorganism inhibiting factors to achieve synergistic action, because exposure to high pressure alone does not ensure the destruction of bacteria in a model system. To create matrixes of raw materials of balanced composition of vegetable raw material, berry press-cakes and meat analogues of legume flour, five variations of balanced composition and nutritional value were created based on beetroot, pumpkin, carrot, black currant, Jerusalem artichoke and legume matrix.